Harnessing the Power of A.I Technologies for Optimal Employee Recruitment and Selection Strategies. - Syeda Rimsha Kazmi; SH. M. Fakhr-e-Alam Siddiqui; Hammad Zafar (LPPM Universitas Negeri Jakarta, 2025)
This research delves deeply into the potential impacts of incorporating artificial intelligence (AI) Technologies on the critical Human Resources Management (HRM) functions of recruitment and selection within organizations. Adopting a rigorous quantitative methodology, the study takes an empirical and descriptive approach, collecting data from 213 participants through a survey using scaling sampling techniques. The collected data was then analyzed using the robust capabilities of Structural Equation Modeling (SEM) in the SmartPLS software 4.0. The study's findings provide strong evidence of the significant influence that AI can have on the core HRM activities of selection and recruitment. These insights hold valuable practical implications for human resources professionals operating in Pakistani organizations, offering implementable suggestions to leverage the power of AI while remaining cautious of potential biases. This research underscores the transformative potential of artificial intelligence within the HRM domain, but also emphasizes the critical need for diligent, ethical, and responsible implementation. By striking the right balance, organizations in Pakistan can harness the efficiency, objectivity, and scalability of AI to enhance their talent acquisition and management capabilities, while simultaneously safeguarding against the pitfalls of algorithmic discrimination and other unintended consequences.